2017
DOI: 10.1108/ijrdm-06-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

Consumer decision making when purchasing eco-friendly apparel

Abstract: Purpose The purpose of this paper is to identify the realistic trade-offs young consumers make when purchasing organic T-shirts. Design/methodology/approach A full profile discrete choice design was used. The data were analysed using a multinomial logit model and desirability indices. Findings Price was the most important attribute to consumers followed by the place of production and then sustainability. Consumers were most willing to purchase T-shirts that are eco-friendly, Made In America, made from wrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 40 publications
0
35
0
3
Order By: Relevance
“…First, the study specifically aims to investigate the role of young Millennials' values and apparel sustainability knowledge in impacting their attitude and willingness to purchase sustainable clothing. Literature supports the assertion that knowledge is a determinant of eco-conscious consumer behaviours, and a lack of knowledge is a constraint (Hill and Lee, 2012;Connell, 2010;Hwang et al, 2015;Rothenberg and Matthews, 2017). Studies have also shown that values influence behavioural decisions and values, as abstract cognitions serve as standards for attitudinal and behavioural processes (Cai and Shannon, 2012;Ma and Lee, 2012).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…First, the study specifically aims to investigate the role of young Millennials' values and apparel sustainability knowledge in impacting their attitude and willingness to purchase sustainable clothing. Literature supports the assertion that knowledge is a determinant of eco-conscious consumer behaviours, and a lack of knowledge is a constraint (Hill and Lee, 2012;Connell, 2010;Hwang et al, 2015;Rothenberg and Matthews, 2017). Studies have also shown that values influence behavioural decisions and values, as abstract cognitions serve as standards for attitudinal and behavioural processes (Cai and Shannon, 2012;Ma and Lee, 2012).…”
Section: Introductionmentioning
confidence: 84%
“…Only when consumers know enough about sustainability can they be likely to purchase sustainable products (Harris et al, 2016;Jensen, 2002;McNeill and Moore, 2015;Park and Kim, 2016;Paul et al, 2016). Consumers with knowledge and concerns regarding environmental and societal issues would be motivated to purchase green and fair trade apparel (Goworek et al, 2012;Hwang et al, 2015;Rothenberg and Matthews, 2017). Researchers have determined that environmental sustainability knowledge is associated with developing attitudes and behavioural patterns that reflect concern for the environment and is a significant predictor of consumption behaviour of environmentally friendly apparel products (Chan, 2001;Chang and Watchravesringkan, 2018;Cowan and Kinley, 2014;Kang et al, 2013;Ko and Jin, 2017).…”
Section: Theoretical Groundingmentioning
confidence: 99%
“…This point is bolstered by the findings of prior studies that examined the relative importance of sustainability. For example, more tangible factors, such as price and fit, were routinely ranked higher than sustainability (Nilssen et al 2019 ; Rothenberg and Matthews 2017 ). In short, while sustainability is an important factor, it is not consumer’s top priority.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de muitas vezes haver um distanciamento entre consciência e atitude, é inegável que a consciência tem forte influência sobre as práticas sustentáveis. Indivíduos que apresentam maior apelo à causa sustentável (Monteiro et al, 2012;Ramirez, Jiménez, & Gau, 2015;Rothenberg & Matthews, 2017) e que praticam valores como autorrespeito, autorrealização e relacionamento caloroso com seus próximos, estão mais próximos do comportamento sustentável (Simões, Giraldi, & Oliveira, 2012).…”
Section: Apresentação E Análise Dos Dadosunclassified
“…A garantia de origem é evidenciada pela informação da origem do produto e também se a produção é local ou não. Produtos de origem em países em desenvolvimento remetem os consumidores a práticas insustentáveis, enquanto em países desenvolvidos geram impressão de cuidado socioambiental (Gruber, Schlegelmilch, & Houston, 2014;Rothenberg & Matthews, 2017). É o caso, por exemplo, da Original Unverpackt (original, sem embalagem), uma empresa Alemã inaugurada em 2014 em Berlin, que trabalha com a venda de produtos sem embalagem, com compras a granel em que os próprios clientes levam as embalagens que possuem em casa ou, se preferirem, podem adquirir saquinhos de papel biodegradável.…”
Section: Atributos Sustentáveis E Percepção Do Consumidorunclassified